PENGARUH AI GENERATIF TERHADAP HASIL BELAJAR KOGNITIF DAN IMPLKASINYA TERHADAP INTEGRITAS AKADEMIK MURID KELAS VIII SMP - Widyawati; Bachri, Syamsul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of Artificial Intelligence (AI) technology has brought about significant transformation in the world of education. This study aims to analyze the effect of AI-generated content on cognitive learning outcomes in social studies and its implications for the academic integrity of eighth-grade junior high school students. This study employed a quantitative method with a one-group pretest-posttest design conducted on 32 students at SMP Negeri 4 Malang. Data analysis was performed using a paired-sample t-test, and the effect was measured using the N-gain score. The results of this study showed an increase in the average learning outcome from 68.66 to 75.69, with a significance level of 0.001 (p < 0.05) and an N-gain score of 0.229 (low-to-moderate category). The use of AI-generated content received a positive response from students, but there was a tendency toward dependency that impacted academic integrity. The use of AI-generated content in social studies instruction has the potential to improve students’ cognitive learning outcomes; however, it requires teacher supervision to ensure that it continues to support ethical and meaningful learning.